Bi-component LPG (Liquefied Petroleum Gas) marine adhesive as well as preparation method and application thereof
Through the design of two-component adhesives, the problem that existing adhesives are difficult to meet the applicable life and curing conditions of LPG ships is solved, and high-performance bonding and curing at different temperatures is achieved, meeting the construction and long-term use needs of LPG ships.
Patent Information
- Application Number
- CN202510159195.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-13
- Publication Date
- 2025-04-11
AI Technical Summary
Existing adhesives are difficult to meet the applicable period and curing conditions of LPG ships at the same time, and cannot effectively meet the performance requirements of LPG ships for construction or long-term adhesive use at low temperatures.
Provided is a two-component LPG marine adhesive, the raw materials include components A and components B. By adjusting component ratios and additives, the pressure bearing capacity, low temperature resistance, adhesive properties and curing rate of the adhesive are improved.
The two-component adhesive maintains a high compression strength and compression elastic modulus from +40°C to -195°C, has good bonding performance, compressive resistance and punch shear resistance, and does not contain heavy metal salts, is safe and environmentally friendly, and complies with the EU Rohs standards.
Abstract
Description
Technical Field
[0001] The present application relates to the field of new material technology, and mainly to a two-component LPG marine adhesive and a preparation method and application thereof. Background Art
[0002] LPG mainly comes from natural gas extraction (about 60%) and oil refining byproducts (about 30%), and is used as fuel (about 70%) and chemical raw materials (about 30%). Currently, US exports and Chinese imports are important factors supporting the LPG market. The US shale gas revolution has led to a significant increase in global LPG supply. At the same time, China's LPG imports have grown strongly driven by the rapid expansion of PDH production capacity, providing strong support for the growth of global LPG shipping trade. In recent years, the global LPG shipping volume has shown an accelerated growth trend. Correspondingly, the growth of LPG ship trade will also drive the demand for LPG marine adhesives.
[0003] According to the survey results, when selecting adhesives for LPG hulls, not only strict performance requirements are required, but also comprehensive performance is required to ensure the stability of LPG ship construction. However, there are currently few load-bearing adhesives with suitable performance in China, so my country's new LPG ships are still using imported adhesives. In addition, imported adhesives have a short service life, a long purchase and stocking cycle, a risk of supply interruption, and there is still room for performance optimization. Therefore, China needs to develop adhesives with better performance than imported adhesives, which is expected to break the monopoly of foreign products.
[0004] In fact, the flexibility and diversity of epoxy material formula design can be adjusted to obtain epoxy resin materials that meet various special performance requirements, and is expected to be widely used in the field of LPG ships. Although epoxy resin cured products have excellent comprehensive performance and are widely used, their shortcomings such as low temperature resistance, brittleness, impact resistance and stress cracking are still the main factors restricting the application of epoxy resin. Moreover, when LPG ships transport liquefied petroleum gas, in order to prevent the temperature from being transferred to the outside of the oil tank and damaging the hull, the adhesive on the outer layer of the oil tank must also have a low thermal conductivity coefficient to block temperature transfer. However, very few adhesives on the market can meet the use conditions of LPG ships. When used in LPG ships, it is easy to have problems with the bonding of steel and birch. In addition, some adhesives contain solvents or other volatile substances, and the volume shrinkage rate is high during curing. When used on the LPG hull, cracks are easily generated, resulting in incomplete bonding. Considering the construction environment and requirements of LPG ships, the adhesive also needs to meet the applicable period of 90-120 minutes to facilitate the use of workers. In addition, the adhesive also needs to meet the curing completion of 48 hours at room temperature, which means that the curing process of the adhesive needs to be fast and controllable. In fact, if the applicable period is required to be relaxed, the curing rate of the adhesive needs to be delayed to a certain extent. However, most adhesives currently cannot meet the applicable period and curing conditions required by LPG ships at the same time, and cannot effectively meet the performance requirements of LPG ship construction or long-term adhesive use. Therefore, the existing technology still needs to be improved and developed. Summary of the invention
[0005] In view of the above-mentioned deficiencies in the prior art, the purpose of the present application is to provide a two-component LPG ship adhesive and a preparation method and application thereof, aiming to solve the problem that the existing adhesives are difficult to simultaneously meet the application period and curing conditions required by LPG ships, and cannot effectively meet the performance requirements of LPG ship construction or long-term adhesive use at low temperatures.
[0006] The technical solution of this application is as follows: In a first aspect, the present application provides a two-component LPG marine adhesive, the raw materials comprising component A and component B, wherein the component A, calculated by mass percentage, comprises the following components: Bisphenol A glycidyl ether epoxy resin 10-40%, alicyclic epoxy resin 2-8%, polyurethane modified epoxy resin 5-10%, rubber 1-2%, glass fiber 10-20%, silicon dioxide 10-30%, aluminum oxide 1-2%, aluminum hydroxide 5-20%, diluent 1-10%, defoamer 0.1-0.5%, silane coupling agent 0.1-0.5%, leveling agent 0.1-0.5%; The B component is calculated by mass percentage and includes the following components: Aliphatic curing agent 10-40%, alicyclic curing agent 10-40%, 4,4'-diaminodiphenylmethane 10-40%, phenolic amine 10-40%, polyether amine 10-40%.
[0007] The two-component LPG marine adhesive provided in this application has a high compressive load-bearing capacity, and as the temperature decreases, the compressive load-bearing capacity increases. Moreover, it still maintains good bonding performance, compressive performance, punch shear performance, hardness, etc. at different temperatures. It does not contain heavy metal salts such as nickel and cobalt, is safe and environmentally friendly, fully complies with EU ROHS standards, does not contain solvents during the processing process, and the wastewater cleaning is non-toxic and harmless. In addition to LPG ships, it can be widely used in aviation, automobiles, construction, furniture, home appliances and other fields.
[0008] Furthermore, the bisphenol A glycidyl ether type epoxy resin is a composition of E51 and E44, and the mass ratio of E51 to E44 is 1:(0.8-1.5).
[0009] Furthermore, the alicyclic epoxy resin is a composition of 2021P and 4221, and the mass ratio of 2021P to 4221 is 1:(0.3-0.5).
[0010] Furthermore, the polyurethane modified epoxy resin is a composition of DER852, DER858 and DER791, and the mass ratio of DER852, DER858 and DER791 is 1:(0.3-0.5):(0.8-1.5).
[0011] Furthermore, the rubber is a composition of butyl rubber, nitrile rubber and polysulfide rubber, and the mass ratio of the butyl rubber, nitrile rubber and polysulfide rubber is 1:(0.3-0.8):(0.3-0.5).
[0012] Furthermore, the glass fiber has a diameter of 1 μm-30 μm and a length of 10 μm-100 μm; The particle size of the silicon dioxide is 10nm~100μm; The particle size of the aluminum oxide is 10 nm to 100 μm; The particle size of the aluminum hydroxide is 10 nm to 100 μm.
[0013] Further, the diluent is one or more of epoxy diluent HK-66, epoxy diluent 501, epoxy diluent 622, epoxy diluent 669, epoxy diluent 690, epoxy diluent X-632, epoxy diluent AGE, epoxy diluent 692, epoxy diluent X-652, epoxy diluent D-691, and epoxy diluent D-678; The defoaming agent is one or more of a polysiloxane defoaming agent, a polyether-modified silicon defoaming agent, a polydimethylsiloxane defoaming agent, and a mineral oil defoaming agent; The silane coupling agent is selected from one or more of vinyl silane coupling agents, chloroalkyl silane coupling agents, aminoalkyl silane coupling agents, epoxyalkyl silane coupling agents, and methacryloyloxyalkyl silane coupling agents; The leveling agent is one or more of a silicone leveling agent, an acrylic leveling agent, and a fluorine leveling agent; The aliphatic curing agent is one or more of diethylenetriamine, triethylenetetramine, tetraethylenepentamine and hexamethylenediamine; The alicyclic curing agent is one or more of 3,5-trimethylcyclohexane, 1,3-cyclohexanedimethylamine and 1,6-cyclohexanediamine.
[0014] Further, the aliphatic curing agent is a composition of diethylenetriamine and triethylenetetramine, and the mass ratio of diethylenetriamine to triethylenetetramine is 1:(0.8-1.5); The alicyclic curing agent is a composition of 3,5-trimethylcyclohexane and 1,6-cyclohexanediamine, and the mass ratio of the 3,5-trimethylcyclohexane to the 1,6-cyclohexanediamine is 1:(0.8-1.5).
[0015] In a second aspect, the present application provides a method for preparing the two-component LPG marine adhesive as described in the first aspect, comprising the following steps: The bisphenol A glycidyl ether epoxy resin, alicyclic epoxy resin, polyurethane modified epoxy resin, rubber, glass fiber, silicon dioxide, aluminum oxide and aluminum hydroxide are mixed in proportion, and then the diluent, defoamer, silane coupling agent and leveling agent are added, and stirred at room temperature to obtain the A component; The aliphatic curing agent, the alicyclic curing agent, 4,4'-diaminodiphenylmethane, phenolic amine and polyether amine are mixed in proportion and stirred at room temperature to obtain the B component.
[0016] In a third aspect, the present application provides an application of the two-component LPG marine adhesive as described in the first aspect, wherein the two-component LPG marine adhesive is applied to a filling connection under a support pad of an oil tank on an LPG ship, comprising the following steps: Add the B component to the A component, stir and react for 30-60 minutes at 250-300 r / min, fill it into the filling connection under the support pad of the oil tank on the LPG ship, and fill the periphery with foam to prevent overflow; Fix the joint and cure at 25-35℃ for 48-72h; The mass ratio of component A to component B is 100-110:9-11.
[0017] Beneficial effects: The two-component LPG marine adhesive provided in the present application does not contain solvents or other volatile substances, has a low volume shrinkage rate during curing, is not prone to cracks after curing and bonding, has little impact on the bonding joints, and ensures long-term bonding effects. Moreover, the two-component LPG marine adhesive can still maintain high compressive strength and compressive elastic modulus at +40°C to -195°C, and has good performance; it has high compressive bearing capacity, and as the temperature decreases, the compressive bearing capacity increases; it still maintains good bonding performance, compressive performance, punch shear performance, hardness, etc. at different temperatures; it has a low thermal conductivity coefficient, which can effectively block the conduction of temperature at the connection, has a heat preservation function, and protects the adhesive from being destroyed by high or low temperature; it has a low expansion coefficient, and during the temperature change process, the solid can have a small change in the amplitude of thermal expansion and contraction, making it safer to use at the connection; it can be used for many assembly operations and is compatible with mechanical fastening methods. Unlike the conventional method, structural adhesives do not damage the substrate (i.e., no drilling is required; there will be no thermal deformation when welding metal); they can bond different materials without electrochemical corrosion; they are suitable for many different geometric structures; they do not produce concentrated pressure in some local locations (thus improving fatigue resistance); they do not need to be repaired or have no bulges (more beautiful). Compared with metals, composite materials can significantly reduce weight while maintaining comparable stiffness; they have excellent environmental and chemical resistance; they are usually formulated as solids (no need to deal with solvent emission issues); they have different curing times and properties; they can adapt to various processing environments and a variety of processing methods, and have good applicability and practicality. The two-component LPG marine adhesive provided in this application does not contain heavy metal salts such as nickel and cobalt, is safe and environmentally friendly, fully complies with EU rohs standards, does not contain solvents during the processing process, and wastewater cleaning is non-toxic and harmless. In addition to LPG ships, it can also be widely used in aviation, automobiles, construction, furniture, home appliances and other fields. DETAILED DESCRIPTION
[0018] The present application provides a two-component LPG marine adhesive and a preparation method and application thereof. To make the purpose, technical solution and effect of the present application clearer and more specific, the present application is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.
[0019] The present application provides a two-component LPG marine adhesive, the raw materials of which include component A and component B, wherein component A, calculated by mass percentage, includes the following components: Bisphenol A glycidyl ether epoxy resin 10-40%, alicyclic epoxy resin 2-8%, polyurethane modified epoxy resin 5-10%, rubber 1-2%, glass fiber 10-20%, silicon dioxide 10-30%, aluminum oxide 1-2%, aluminum hydroxide 5-20%, diluent 1-10%, defoamer 0.1-0.5%, silane coupling agent 0.1-0.5%, leveling agent 0.1-0.5%; Component B, calculated by mass percentage, includes the following components: Aliphatic curing agent 10-40%, alicyclic curing agent 10-40%, 4,4'-diaminodiphenylmethane 10-40%, phenolic amine 10-40%, polyether amine 10-40%.
[0020] This application adds alicyclic epoxy resin, and the alicyclic skeleton can directly act on the inside of the epoxy resin as a group structure. When used together with bisphenol A glycidyl ether epoxy resin, it can increase the crosslinking density, thereby improving the bonding performance. The two-component LPG marine adhesive provided has high compressive bearing capacity, compressive performance, punch shear resistance, hardness, etc. It does not contain heavy metal salts such as nickel and cobalt, is safe and environmentally friendly, and fully complies with EU ROHS standards. The processing process does not contain solvents, and the wastewater cleaning is non-toxic and harmless. In addition to LPG ships, it can also be widely used in aviation, automobiles, construction, furniture, home appliances and other fields.
[0021] Specifically, LPG needs to be stored and transported at a lower temperature via LPG ships, which also places higher requirements on the use of adhesives, but there are very few load-bearing adhesives that can be used at +40°C to -195°C. Traditional adhesives become more brittle at low temperatures, crack more quickly during compression, and are more likely to break into pieces after compression, which poses a greater risk when used in LPG ships. In addition, the performance of traditional adhesives will be reduced to 5-7 MPa in tensile strength at -45°C, and it is impossible to maintain above 15MPa, which means that applying a small force at low temperatures will cause the bond to break. The two-component LPG marine adhesive prepared in this application also has good low-temperature resistance, maintains good bonding performance at different temperatures, is not prone to brittle fracture at low temperatures, and its compressive load-bearing capacity increases as the temperature decreases.
[0022] Furthermore, the bisphenol A glycidyl ether epoxy resin is a composition of E51 and E44, and the mass ratio of E51 to E44 is 1:(0.8-1.5), preferably 1:1.35. Among them, E51 is a colorless viscous liquid with a molecular formula of C 21 H 24 O4, epoxy value is 0.55~0.56, no softening point; E51 is a colorless viscous liquid, the molecular formula is C 21 H 24O4, epoxy value is 0.41~0.47, softening point is 12-20℃.
[0023] In the present application, the addition of bisphenol A glycidyl ether type epoxy resin can achieve good adhesive performance, so that the adhesive not only has excellent adhesion, cold resistance, salt spray resistance, but also has good wear resistance and antioxidant properties. After long-term research, the inventor also found that in the present application, when the mass ratio of E51 and E44 is 1: (0.8-1.5), especially 1: 1.35, the present application has very good iron sheet bonding performance, compression resistance and curing speed for the adhesive. The inventor speculates that E51 and E44 are both bisphenol A glycidyl ether type epoxy resins. After reacting with a curing agent, the cross-linking density of the adhesive is strengthened, wherein the bonding performance of E44 is stronger than that of E51, and the curing speed is faster, while E51 has a higher hardness and good corrosion resistance. Combining the advantages of the two, after adjusting the ratio, the bonding performance and compression resistance of the adhesive can be improved.
[0024] Furthermore, the alicyclic epoxy resin is a composition of 2021P and 4221, and the mass ratio of 2021P to 4221 is 1:(0.3-0.5). Among them, 2021P is a colorless, transparent, viscous liquid, and its molecular formula is C 14 H 20 O4, purity 99%, epoxy equivalent is 130-135.
[0025] In the present application, the selected alicyclic epoxy resin composition can further improve the bonding performance, reduce viscosity, improve the resin's anti-aging ability and reduce the curing shrinkage rate, ensuring that the bonding performance at low temperatures can meet the use requirements of LPG ships. The inventor speculates that 2021P has a better cross-linking effect with bisphenol A glycidyl ether type epoxy resin. The alicyclic structure of 2021P can act on the inside of the epoxy resin and act as a skeleton to improve the bonding strength. 4221 has low viscosity, good heat resistance, corrosion resistance, UV resistance, radiation resistance, weather resistance, small curing shrinkage, and can improve the resin's anti-aging ability and reduce the curing shrinkage rate.
[0026] Further, the polyurethane modified epoxy resin is a composition of DER852, DER858 and DER791, and the mass ratio of DER852, DER858 and DER791 is 1:(0.3-0.5):(0.8-1.5). Among them, DER852 is a brown viscous liquid with a viscosity of 7000-12000 cps and an epoxy equivalent of 310-330; DER858 is a yellow to brown viscous liquid with a viscosity of 2800-42000 cps and an epoxy equivalent of 380-420; DER791 is a colorless transparent viscous liquid with a viscosity of 35000-45000 cps and an epoxy equivalent of 235-270.
[0027] In the present application, the selected polyurethane modified epoxy resin composition can further improve toughness and bonding ability, ensuring that the bonding performance at low temperature can meet the use requirements of LPG ships. The inventor speculates that the polyurethane modified epoxy resin contains polyurethane groups, and the rigid epoxy resin phase and the polyurethane elastic phase are entangled with each other to form an interpenetrating polymer network structure, and produce "forced miscibility" and "synergistic effect", thereby improving toughness and bonding ability.
[0028] Further, the rubber is one or more of butyl rubber, nitrile rubber and polysulfide rubber in the synthetic rubber. Preferably, the rubber is a composition of butyl rubber, nitrile rubber and polysulfide rubber, and the mass ratio of butyl rubber, nitrile rubber and polysulfide rubber is 1: (0.3-0.8): (0.3-0.5). Among them, butyl rubber is a polymer of isobutylene and a small amount of isoprene or butadiene, with a molecular weight of 2000-30000; nitrile rubber is a polymer of butadiene and acrylonitrile, with a molecular weight of 2000-30000; polysulfide rubber is a disulfide polymer of ethylene formal, with a molecular weight of 800-6000.
[0029] In the present application, adding butyl rubber, nitrile rubber and polysulfide rubber in appropriate proportions can further improve the bonding performance and toughness, ensuring that the bonding performance at low temperatures can meet the use requirements of LPG ships.
[0030] Furthermore, the selected glass fiber is a fiber powder solid with a diameter of 1 μm-30 μm and a length of 10 μm-100 μm.
[0031] In the present application, the mechanical properties, corrosion resistance, heat resistance, electrical insulation and dielectric properties can be further improved by adding glass fiber, and the glass fiber has good adhesion to the epoxy resin. After the glass fiber is added, it is interspersed in the network structure of the polymer to make the structure tighter, which is beneficial to improve important properties such as compression resistance and bonding.
[0032] Furthermore, the selected silicon dioxide is a granular powder solid with a particle size of 10nm~100μm.
[0033] In the present application, the hardness, mechanical properties, corrosion resistance and heat resistance of the adhesive after curing can be improved by adding silicon dioxide.
[0034] Furthermore, the selected aluminum oxide is a granular powder solid with a particle size of 10nm~100μm.
[0035] In the present application, the bonding strength, mechanical properties, toughness, etc. can be improved by adding alumina.
[0036] Furthermore, the selected aluminum hydroxide is a granular powder solid with a particle size of 10nm~100μm.
[0037] In the present application, the compressive strength, hardness, mechanical properties, etc. can be improved by adding aluminum hydroxide. By controlling the particle size range of the filler, the comprehensive performance of the adhesive can be improved. The smaller the particle size, the higher the dispersion, the better the toughness, and the higher the shear strength; the higher the particle size, the higher the hardness and the higher the compressive strength.
[0038] Furthermore, the diluent is selected from one or more of active diluents or inactive diluents; further, the diluent is one or more of epoxy diluent HK-66, epoxy diluent 501, epoxy diluent 622, epoxy diluent 669, epoxy diluent 690, epoxy diluent X-632, epoxy diluent AGE, epoxy diluent 692, epoxy diluent X-652, epoxy diluent D-691, and epoxy diluent D-678.
[0039] In the present application, the adhesive provided needs to flow into the connection gap during use, which requires the resin to have good fluidity. The role of the diluent is to reduce the viscosity and improve the fluidity of the resin.
[0040] Furthermore, the defoaming agent is one or more of a polysiloxane defoaming agent, a polyether-modified silicon defoaming agent, a polydimethylsiloxane defoaming agent, and a mineral oil defoaming agent.
[0041] In the present application, the adhesive is prone to have many bubbles during production, which may reduce the compression and shear properties of the adhesive. The role of the defoaming agent is to promote the rupture of bubbles or inhibit the generation of bubbles during the production process of the adhesive.
[0042] Furthermore, the silane coupling agent is selected from one or more of vinyl silane coupling agents, chloroalkyl silane coupling agents, aminoalkyl silane coupling agents, epoxyalkyl silane coupling agents, and methacryloxyalkyl silane coupling agents.
[0043] In this application, the silane coupling agent can hydrolyze to form a bond between the organic and inorganic interfaces, promoting interface fusion. The selected silane coupling agent is mainly used for the coupling effect between the glass fiber and the resin, which is beneficial to enhance the bonding performance of the adhesive and improve the tightness of the polymer structure.
[0044] Furthermore, the leveling agent is one or more of a silicone leveling agent, an acrylic leveling agent, and a fluorine leveling agent.
[0045] In this application, the adhesive needs to maintain a flat surface in actual application, and the role of the leveling agent is to enable the resin to form a flat, smooth and uniform surface during the curing process.
[0046] Furthermore, the aliphatic curing agent is one or more of diethylenetriamine, triethylenetetramine, tetraethylenepentamine, and hexamethylenediamine. Preferably, the aliphatic curing agent is a combination of diethylenetriamine and triethylenetetramine, and the mass ratio of diethylenetriamine to triethylenetetramine is 1:(0.8-1.5). Among them, diethylenetriamine is a yellow viscous liquid with a molecular formula of C4H 13 N3, amine value is 9.6; triethylenetetramine is a yellow viscous liquid, the molecular formula is C6H 18 N4, amine value is 38.8.
[0047] In the present application, the inventors found that the use of a composition of diethylenetriamine and triethylenetetramine as an aliphatic curing agent can improve the hardness, mechanical properties, curing rate and shorten the curing time of the adhesive.
[0048] Furthermore, the alicyclic curing agent is one or more of 3,5-trimethylcyclohexane, 1,3-cyclohexanedimethylamine and 1,6-cyclohexanediamine. Preferably, the alicyclic curing agent is a combination of 3,5-trimethylcyclohexane and 1,6-cyclohexanediamine, and the mass ratio of 3,5-trimethylcyclohexane to 1,6-cyclohexanediamine is 1:(0.8-1.5). Among them, 3,5-trimethylcyclohexane is a colorless viscous liquid with a molecular formula of C 10 H 22 N2, amine value is 24.4; 1,6-cyclohexanediamine is a colorless viscous liquid, molecular formula C6H 16 N2, amine value is 28.
[0049] In the present application, the alicyclic curing agent composition used can improve the corrosion resistance, compression resistance, compression modulus, hardness, etc. of the adhesive.
[0050] Specifically, in the present application, the selected 4,4'-diaminodiphenylmethane is a light yellow solid with a molecular formula of C 13 H 14 N2, the amine value is 52.5, and the compression resistance, compression modulus, hardness, etc. can be improved by adding 4,4'-diaminodiphenylmethane.
[0051] The selected phenolic amine is a yellow viscous liquid with the molecular formula [RNHCH2C6H4OH] n The amine value is 97. By adding phenolic amine, the bonding performance, toughness, mechanical properties, etc. can be improved.
[0052] The selected polyetheramine is a colorless, transparent, viscous liquid with a molecular formula of C 3n+3 H 6n+10 O n N2, molecular weight is 230-5000, amine value is 115, and the addition of polyetheramine can improve the bonding performance, toughness, mechanical properties, etc.
[0053] The present application also provides a method for preparing the two-component LPG marine adhesive as described above, which comprises the following steps: Bisphenol A glycidyl ether epoxy resin, alicyclic epoxy resin, polyurethane modified epoxy resin, rubber, glass fiber, silicon dioxide, aluminum oxide and aluminum hydroxide are mixed in proportion, and then a diluent, a defoaming agent, a silane coupling agent and a leveling agent are added, and stirred at room temperature to obtain component A.
[0054] The aliphatic curing agent, the alicyclic curing agent, 4,4'-diaminodiphenylmethane, the phenolic amine and the polyether amine are mixed in proportion and stirred at room temperature to obtain component B.
[0055] The two-component LPG marine adhesive can be obtained by mixing component A and component B. Specifically, when using, component B can also be added to component A first, and then stirred at 250-300r / min for 30-60min. The mass ratio of component A to component B is 100-110:9-11.
[0056] The present application also provides an application of the two-component LPG marine adhesive as described above, wherein the two-component LPG marine adhesive is applied to the filling connection under the support pad of the oil tank on the LPG ship, comprising the following steps: Add component B to component A, stir and react for 30-60 minutes at 250-300r / min, fill it into the filling connection under the support pad of the oil tank on the LPG ship, and fill the periphery with foam to prevent overflow; Fix the joints and cure at 25-35°C for 48-72 hours.
[0057] Among them, the mass ratio of component A to component B is 100~110:9~11.
[0058] Specifically, in the present application, after component A and component B are mixed, the applicable period is 90-120 minutes, and the use can be adjusted within this time range. The connection position can be determined and then the connection can be fixed. After the curing is completed, the degree of curing can be measured and confirmed by a Barcol hardness tester. A hardness of 25-30 Barcol can be considered to be basically cured, and a hardness of 45-55 Barcol can be considered to be completely cured.
[0059] The invention is further described below by means of specific examples.
[0060] Example 1 Embodiment 1 provides a two-component LPG marine adhesive, wherein the A component comprises the following components by mass percentage: 20% of bisphenol A glycidyl ether epoxy resin, 4% of alicyclic epoxy resin, 6% of polyurethane modified epoxy resin, 1% of rubber, 20% of glass fiber, 30% of silicon dioxide, 1% of aluminum oxide, 11.5% of aluminum hydroxide, 5% of diluent, 0.5% of defoamer, 0.5% of silane coupling agent, and 0.5% of leveling agent. The B component comprises the following components: 20% of aliphatic curing agent, 20% of alicyclic curing agent, 20% of 4,4'-diaminodiphenylmethane, 20% of phenolic amine, and 20% of polyetheramine.
[0061] Among them, the bisphenol A glycidyl ether type epoxy resin is a combination of E51 and E44 models, and the corresponding mass ratio is 1:0.8; the alicyclic epoxy resin is a combination of 2021P and 4221 models, and the corresponding mass ratio is 1:0.5; the polyurethane modified epoxy resin is DER 852, DER 858 and DER The composition of model 791 is 1:0.5:0.8 in mass ratio; the rubber is a composition of butyl rubber, nitrile rubber and polysulfide rubber in mass ratio of 1:0.3:0.3; the glass fiber has a diameter of 5 μm and a length of 50 μm; the silica particle size is 50 μm; the alumina particle size is 50 μm; the aluminum hydroxide particle size is 50 μm; the active diluent is selected from epoxy diluent HK-66; the defoamer is selected from polysiloxane defoamer; the silane coupling agent is selected from vinyl silane coupling agent; the leveling agent is selected from silicone leveling agent; the aliphatic curing agent is a composition of diethylenetriamine and triethylenetetramine in mass ratio of 1:1; the alicyclic curing agent is a composition of 3,5-trimethylcyclohexane and 1,6-cyclohexanediamine in mass ratio of 1:1; the molecular weight of the polyetheramine is 2000.
[0062] The preparation method of the two-component LPG marine adhesive of Example 1 comprises the following steps: Bisphenol A glycidyl ether epoxy resin, alicyclic epoxy resin, polyurethane modified epoxy resin, rubber, glass fiber, silicon dioxide, aluminum oxide and aluminum hydroxide are mixed in proportion, and then a diluent, a defoaming agent, a silane coupling agent and a leveling agent are added, and stirred at room temperature to obtain component A.
[0063] The aliphatic curing agent, the alicyclic curing agent, 4,4'-diaminodiphenylmethane, the phenolic amine and the polyether amine are mixed in proportion and stirred at room temperature to obtain component B.
[0064] Component B was added to component A, and the mixture was stirred and reacted at 250-300 r / min for 30-60 min to obtain the two-component LPG marine adhesive of Example 1.
[0065] Among them, the mass ratio of component A to component B is 10:1.
[0066] Example 2 Embodiment 2 provides a two-component LPG marine adhesive, wherein component A comprises the following components by mass percentage: 27.7% bisphenol A glycidyl ether epoxy resin, 4% alicyclic epoxy resin, 6% polyurethane modified epoxy resin, 1% rubber, 20% glass fiber, 20% silicon dioxide, 1% aluminum oxide, 15% aluminum hydroxide, 5% diluent, 0.1% defoamer, 0.1% silane coupling agent, and 0.1% leveling agent. Component B comprises the following components: 20% aliphatic curing agent, 20% alicyclic curing agent, 20% 4,4'-diaminodiphenylmethane, 20% phenolic amine, and 20% polyetheramine.
[0067] Among them, the bisphenol A glycidyl ether type epoxy resin is a combination of E51 and E44 models, and the corresponding mass ratio is 1:0.8; the alicyclic epoxy resin is a combination of 2021P and 4221 models, and the corresponding mass ratio is 1:0.5; the polyurethane modified epoxy resin is DER 852, DER 858 and DER The composition of model 791 is 1:0.5:0.8 in mass ratio; the rubber is a composition of butyl rubber, nitrile rubber and polysulfide rubber in mass ratio of 1:0.3:0.3; the glass fiber has a diameter of 4 μm and a length of 50 μm; the silica particle size is 10 μm; the alumina particle size is 30 μm; the aluminum hydroxide particle size is 10 μm; the active diluent is selected from epoxy diluent HK-66; the defoamer is selected from polysiloxane defoamer; the silane coupling agent is selected from vinyl silane coupling agent; the leveling agent is selected from silicone leveling agent; the aliphatic curing agent is a composition of diethylenetriamine and triethylenetetramine in mass ratio of 1:0.8; the alicyclic curing agent is a composition of 3,5-trimethylcyclohexane and 1,6-cyclohexanediamine in mass ratio of 1:0.8; the molecular weight of the polyetheramine is 2000.
[0068] The two-component LPG marine adhesive of Example 2 was prepared by the same preparation method as Example 1.
[0069] Example 3 Embodiment 3 provides a two-component LPG marine adhesive, wherein the A component comprises the following components by mass percentage: 20% of bisphenol A glycidyl ether epoxy resin, 4% of alicyclic epoxy resin, 6% of polyurethane modified epoxy resin, 1% of rubber, 20% of glass fiber, 22.7% of silicon dioxide, 1% of aluminum oxide, 20% of aluminum hydroxide, 5% of diluent, 0.1% of defoamer, 0.1% of silane coupling agent, and 0.1% of leveling agent. The B component comprises the following components: 20% of aliphatic curing agent, 20% of alicyclic curing agent, 20% of 4,4'-diaminodiphenylmethane, 20% of phenolic amine, and 20% of polyetheramine.
[0070] Among them, the bisphenol A glycidyl ether type epoxy resin is a combination of E51 and E44 models, and the corresponding mass ratio is 1:1; the alicyclic epoxy resin is a combination of 2021P and 4221 models, and the corresponding mass ratio is 1:0.5; the polyurethane modified epoxy resin is DER 852, DER 858 and DER The composition of model 791 is 1:0.3:1 in mass ratio; the rubber is a composition of butyl rubber, nitrile rubber and polysulfide rubber in mass ratio of 1:0.5:0.5; the glass fiber has a diameter of 2 μm and a length of 30 μm; the silica particle size is 10 μm; the alumina particle size is 10 μm; the aluminum hydroxide particle size is 10 μm; the active diluent is selected from epoxy diluent HK-66; the defoamer is selected from polysiloxane defoamer; the silane coupling agent is selected from vinyl silane coupling agent; the leveling agent is selected from silicone leveling agent; the aliphatic curing agent is a composition of diethylenetriamine and triethylenetetramine in mass ratio of 1:1; the alicyclic curing agent is a composition of 3,5-trimethylcyclohexane and 1,6-cyclohexanediamine in mass ratio of 1:1; the molecular weight of the polyetheramine is 4000.
[0071] The two-component LPG marine adhesive of Example 3 was prepared by the same preparation method as Example 1.
[0072] Example 4 Example 4 provides a two-component LPG marine adhesive, wherein component A comprises the following components by mass percentage: 20% bisphenol A glycidyl ether epoxy resin, 8% alicyclic epoxy resin, 10% polyurethane modified epoxy resin, 1% rubber, 20% glass fiber, 24.7% silicon dioxide, 1% aluminum oxide, 10% aluminum hydroxide, 5% diluent, 0.1% defoamer, 0.1% silane coupling agent, and 0.1% leveling agent. Component B comprises the following components: 10% aliphatic curing agent, 20% alicyclic curing agent, 30% 4,4'-diaminodiphenylmethane, 20% phenolic amine, and 20% polyetheramine.
[0073] Among them, the bisphenol A glycidyl ether type epoxy resin is a combination of E51 and E44 models, and the corresponding mass ratio is 1:0.8; the alicyclic epoxy resin is a combination of 2021P and 4221 models, and the corresponding mass ratio is 1:0.5; the polyurethane modified epoxy resin is DER 852, DER 858 and DER The composition of model 791 is 1:0.5:0.8 in mass ratio; the rubber is a composition of butyl rubber, nitrile rubber and polysulfide rubber in mass ratio of 1:0.3:0.3; the glass fiber has a diameter of 5 μm and a length of 50 μm; the silica particle size is 50 μm; the alumina particle size is 50 μm; the aluminum hydroxide particle size is 50 μm; the active diluent is selected from epoxy diluent HK-66; the defoamer is selected from polysiloxane defoamer; the silane coupling agent is selected from vinyl silane coupling agent; the leveling agent is selected from silicone leveling agent; the aliphatic curing agent is a composition of diethylenetriamine and triethylenetetramine in mass ratio of 1:1; the alicyclic curing agent is a composition of 3,5-trimethylcyclohexane and 1,6-cyclohexanediamine in mass ratio of 1:1; the molecular weight of the polyetheramine is 2000.
[0074] The two-component LPG marine adhesive of Example 4 was prepared by the same preparation method as Example 1.
[0075] Example 5 Example 5 provides a two-component LPG marine adhesive, wherein component A comprises the following components by mass percentage: 20% bisphenol A glycidyl ether epoxy resin, 4% alicyclic epoxy resin, 6% polyurethane modified epoxy resin, 1% rubber, 20% glass fiber, 30% silicon dioxide, 1% aluminum oxide, 12.7% aluminum hydroxide, 5% diluent, 0.1% defoamer, 0.1% silane coupling agent, and 0.1% leveling agent. Component B comprises the following components: 20% aliphatic curing agent, 20% alicyclic curing agent, 20% 4,4'-diaminodiphenylmethane, 20% phenolic amine, and 20% polyetheramine.
[0076] Among them, the bisphenol A glycidyl ether type epoxy resin is a combination of E51 and E44 models, and the corresponding mass ratio is 1:0.8; the alicyclic epoxy resin is a combination of 2021P and 4221 models, and the corresponding mass ratio is 1:0.5; the polyurethane modified epoxy resin is DER 852, DER 858 and DER The composition of model 791 is 1:0.5:0.8 in mass ratio; the rubber is a composition of butyl rubber, nitrile rubber and polysulfide rubber in mass ratio of 1:0.3:0.3; the glass fiber has a diameter of 2 μm and a length of 50 μm; the silica particle size is 50 μm; the alumina particle size is 50 μm; the aluminum hydroxide particle size is 50 μm; the active diluent is selected from epoxy diluent HK-66; the defoamer is selected from polysiloxane defoamer; the silane coupling agent is selected from vinyl silane coupling agent; the leveling agent is selected from silicone leveling agent; the aliphatic curing agent is a composition of diethylenetriamine and triethylenetetramine in mass ratio of 1:1; the alicyclic curing agent is a composition of 3,5-trimethylcyclohexane and 1,6-cyclohexanediamine in mass ratio of 1:1; the molecular weight of the polyetheramine is 2000.
[0077] The two-component LPG marine adhesive of Example 5 was prepared by the same preparation method as Example 1.
[0078] Example 6 Example 6 provides a two-component LPG marine adhesive, wherein component A comprises the following components by mass percentage: 20% bisphenol A glycidyl ether epoxy resin, 4% alicyclic epoxy resin, 6% polyurethane modified epoxy resin, 1% rubber, 20% glass fiber, 30% silicon dioxide, 1% aluminum oxide, 12.7% aluminum hydroxide, 5% diluent, 0.1% defoamer, 0.1% silane coupling agent, and 0.1% leveling agent. Component B comprises the following components: 20% aliphatic curing agent, 20% alicyclic curing agent, 20% 4,4'-diaminodiphenylmethane, 20% phenolic amine, and 20% polyetheramine.
[0079] Among them, the bisphenol A glycidyl ether type epoxy resin is E51; the alicyclic epoxy resin is 4221; the polyurethane modified epoxy resin is DER 852; the rubber is butyl rubber; the glass fiber has a diameter of 4μm and a length of 50μm; the silica particle size is 50μm; the alumina particle size is 10μm; the aluminum hydroxide particle size is 50μm; the active diluent is selected from epoxy diluent HK-66; the defoamer is selected from polysiloxane defoamer; the silane coupling agent is selected from vinyl silane coupling agent; the leveling agent is selected from silicone type leveling agent; the aliphatic curing agent is diethylenetriamine; the alicyclic curing agent is 3,5-trimethylcyclohexane; the molecular weight of the polyetheramine is 400.
[0080] The two-component LPG marine adhesive of Example 6 was prepared by the same preparation method as Example 1.
[0081] Comparative Example 1 Comparative Example 1 provides an adhesive, wherein component A comprises the following components, calculated by mass percentage: 5% bisphenol A glycidyl ether epoxy resin, 20% alicyclic epoxy resin, 20% polyurethane modified epoxy resin, 5% rubber, 10% glass fiber, 10% silicon dioxide, 10% aluminum oxide, 5% aluminum hydroxide, 12% diluent, 1% defoamer, 1% silane coupling agent, and 1% leveling agent. Component B comprises the following components: 15% aliphatic curing agent, 15% alicyclic curing agent, 40% 4,4'-diaminodiphenylmethane, 15% phenolic amine, and 15% polyetheramine.
[0082] Among them, the bisphenol A glycidyl ether type epoxy resin is E44 model; the alicyclic epoxy resin is 2021P model; the polyurethane modified epoxy resin is DER 858 model; the rubber is nitrile rubber; the glass fiber has a diameter of 50μm and a length of 150μm; the silica particle size is 150μm; the alumina particle size is 150μm; the aluminum hydroxide particle size is 150μm; the active diluent is selected from epoxy diluent HK-66; the defoamer is selected from polysiloxane defoamer; the silane coupling agent is selected from vinyl silane coupling agent; the leveling agent is selected from silicone leveling agent; the aliphatic curing agent is a composition of diethylenetriamine and triethylenetetramine, and the corresponding mass ratio is 1:1; the alicyclic curing agent is a composition of 3,5-trimethylcyclohexane and 1,6-cyclohexanediamine, and the corresponding mass ratio is 1:1; the molecular weight of the polyetheramine is 2000.
[0083] The adhesive of Comparative Example 1 was prepared by the same preparation method as Example 1.
[0084] Comparative Example 2 Comparative Example 2 provides an adhesive, wherein component A includes the following components, calculated by mass percentage: 20% alicyclic epoxy resin, 20% polyurethane modified epoxy resin, 6% rubber, 10% glass fiber, 10% alumina, 5% aluminum hydroxide, 20% diluent, 3% defoamer, 3% silane coupling agent, and 3% leveling agent. Component B includes the following components: 50% aliphatic curing agent and 50% polyetheramine.
[0085] Among them, the alicyclic epoxy resin is model 2021P; the polyurethane modified epoxy resin is model DER 858; the rubber is nitrile rubber; the glass fiber has a diameter of 50 μm and a length of 150 μm; the alumina particle size is 150 μm; the aluminum hydroxide particle size is 150 μm; the active diluent is selected from epoxy diluent HK-66; the defoaming agent is selected from polysiloxane defoaming agent; the silane coupling agent is selected from vinyl silane coupling agent; the leveling agent is selected from silicone leveling agent; the aliphatic curing agent is diethylenetriamine; and the molecular weight of the polyetheramine is 2000.
[0086] The adhesive of Comparative Example 2 was prepared by the same preparation method as Example 1.
[0087] Comparative Example 3 Comparative Example 3 provides an adhesive, wherein component A comprises the following components, calculated by mass percentage: 20% alicyclic epoxy resin, 20% polyurethane modified epoxy resin, 6% rubber, 10% glass fiber, 10% alumina, 5% aluminum hydroxide, 20% diluent, 3% defoamer, 3% silane coupling agent, and 3% leveling agent. Component B comprises the following components: 5% aliphatic curing agent, 50% 4,4'-diaminodiphenylmethane, and 45% phenolic amine.
[0088] Among them, the alicyclic epoxy resin is model 2021P; the polyurethane modified epoxy resin is model DER 858; the rubber is nitrile rubber; the glass fiber has a diameter of 50 μm and a length of 150 μm; the alumina particle size is 150 μm; the aluminum hydroxide particle size is 150 μm; the active diluent is selected from epoxy diluent HK-66; the defoaming agent is selected from polysiloxane defoaming agent; the silane coupling agent is selected from vinyl silane coupling agent; the leveling agent is selected from silicone leveling agent; the aliphatic curing agent is a combination of diethylenetriamine and triethylenetetramine, and the corresponding mass ratio is 1:1.
[0089] The adhesive of Comparative Example 3 was prepared by the same preparation method as Example 1.
[0090] Performance Evaluation 1. Compression test: According to the standard test method ASTM D-695, the compression strength, compression modulus and compression toughness of the adhesive are tested. The finished product samples of the adhesive of the embodiment and the comparative example are prepared for testing, and the sample sizes are 12.7mm×12.7mm×25.4mm and 12.7mm×12.7mm×50.8mm. The compression strength of the adhesive is tested at 20°C, -50°C, -110°C and -196°C, and its compression modulus and compression toughness are calculated, and 5 parallel experiments are performed.
[0091] 2. Bonding shear test of steel and birch: The adhesive was tested for bonding shear test on steel and birch according to the standard test method ASTM D-1002. The size of the steel and birch was 1.6×25.4×100 mm, the bonding overlap thickness was 12.5 mm, and the adhesives of the test examples and comparative examples were tested for bonding shear test on steel and birch at 40°C, 20°C and -45°C, respectively, and 5 parallel experiments were performed.
[0092] 3. Viscosity test: The viscosity of the adhesive was tested according to the standard test method ASTM D-2196. The viscosity of the two components of the adhesive in the examples and comparative examples at room temperature was tested using a viscometer, and five parallel experiments were performed.
[0093] 4. Hardness test: The hardness of the adhesive was tested according to the standard test method ASTM D-2583. The hardness of the adhesives of the examples and comparative examples after complete curing at room temperature was tested using a Barcol hardness tester, and five parallel experiments were performed.
[0094] 5. Tensile test: The tensile strength of the adhesive was tested according to the standard test method ASTM D-638. Dumbbell Type 1 specimens were prepared, and the elongation at break of the finished adhesives of the embodiment and the comparative example was tested respectively, and 5 parallel experiments were performed.
[0095] 6. Thermal expansion coefficient test: The thermal expansion coefficient of the adhesive was tested according to the standard test method ASTM D-696. The adhesives of the examples and comparative examples were prepared into rectangular blocks with a size of 12.5×6.3×(50-125) mm, and the thermal expansion coefficient of the adhesive was tested at a temperature of -30°C to 30°C, and 5 parallel experiments were performed.
[0096] 7. Thermal conductivity test: The thermal conductivity of the adhesive was tested according to the standard test method ASTM D-5470. The adhesives of the examples and comparative examples were respectively prepared into cylinders with a size of 20×6 mm, and the thermal conductivity of the adhesives was tested at room temperature, and 5 parallel experiments were performed.
[0097] 8. Punch shear test: The punch shear strength of the adhesive was tested according to the standard test method ASTM D-732. The adhesives of the examples and comparative examples were prepared into discs with a diameter of 50 mm, a thickness of 1.27-12.7 mm, and a hole of 11 mm in the middle. The punch shear strength was tested and five parallel experiments were performed.
[0098] 9. Creep test: According to the internal standard test of the creep test of the adhesive, the adhesive of Examples 1-5 was prepared into a cube with a size of 30×30×30 mm, and was continuously compressed with 2MPa for 120 hours. The compression displacement was tested and 5 parallel experiments were performed. Internal standard of creep test: The test will continuously compress 3 samples with a size of 30*30*30mm for 120 hours at 300psi (=2MPa). Measure the thickness of each sample; the force applied to the object = stress * the force area of the object (F=ơ*A=2*30*30=1800N), load (a). The height of the object before compression, load (b). The height of the object after compression for 120 hours, and detect the height difference before and after compression for 120 hours. It is generally required that (ab) / a<0.053 under 120 hours of compression creep.
[0099] 10. Curing shrinkage test: The curing shrinkage of the adhesive was tested according to the standard test method ASTM D-2566. The adhesive raw materials of the embodiment and the comparative example were poured into the mold, the length and area before and after curing were measured, and the shrinkage after curing was calculated. Five parallel experiments were performed.
[0100] 11. Curing time test: The curing time of the adhesive was tested according to the standard test method ASTM D-2583. During the curing process of the adhesives of the embodiment and the comparative example, the Barcol hardness was tested every 12 hours, and the final curing time was determined when the Barcol hardness reached 38 or above. Five parallel experiments were performed.
[0101] 12. Application period test: The pot life of the adhesive was tested according to GB / T 7123.1-2002. The pot life refers to the time that the mixed adhesive can be used for construction after the resin and the curing agent are mixed. The adhesive raw materials of the embodiment and the comparative example were dipped into a wooden board, and the adhesive was dripped vertically to observe the fluidity of the liquid. The flow and dripping of the liquid were recorded every 5 minutes. The final time when the liquid stopped flowing and dripping was recorded as the pot life. Five parallel experiments were performed.
[0102] The test results of the performance evaluation of Examples 1-3 are shown in Table 1: Table 1 Test items Test Standards Example 1 Example 2 Example 3 Compression strength ASTMD-695 137 MPa(20℃)248 MPa(-50℃)365 MPa(-110℃)295 MPa(-196℃) 129 MPa(20℃)242 MPa(-50℃)378 MPa(-110℃)283 MPa(-196℃) 132MPa(20℃)224MPa(-50℃)358MPa(-110℃)262MPa(-196℃) Compression modulus ASTMD-695 5757 MPa (20℃) 6120 MPa (-50℃) 7089 MPa (-110℃) 7203MPa (-196℃) 5860 MPa (20℃) 6730 MPa (-50℃) 7190 MPa (-110℃) 7930MPa (-196℃) 5750 MPa(20℃)6690 MPa(-50℃)7093 MPa(-110℃)8030MPa(-196℃) Compression toughness ASTMD-695 748 MPa(20℃)647 MPa(-50℃)1047 MPa(-110℃)553 MPa(-196℃) 752 MPa(20℃)649 MPa(-50℃)1176 MPa(-110℃)633 MPa(-196℃) 721 MPa(20℃)629 MPa(-50℃)1052 MPa(-110℃)610 MPa(-196℃) Bonding of steel ASTMD-1002 12 MPa(40℃)15 MPa(20℃)8MPa(-45℃) 17 MPa(40℃)20 MPa(20℃)11MPa(-45℃) 15 MPa(40℃)14 MPa(20℃)10MPa(-45℃) Birch Bonding ASTMD-1002 4.2 MPa (40℃) 4.4 MPa (20℃) 4.1 MPa (-45℃) Adhesive surface remains bonded, breaking from the wood board 4.1 MPa (40℃) 4.8 MPa (20℃) 4.5 MPa (-45℃) Adhesive surface remains bonded, breaking from the wood board 4.7 MPa (40℃) 4.0 MPa (20℃) 4.0 MPa (-45℃) Adhesive surface remains bonded, breaking from the wood board Viscosity ASTMD-2196 Component A - 10,250 cps Component B - 48 cps Component A - 10,300 cps Component B - 32 cps Component A - 10,230 cps Component B - 40 cps hardness ASTMD-2583 48Hbr 45 Hbr 49 Hb Stretch ASTMD-638 4.6% 5.1% 4.8% Coefficient of thermal expansion ASTMD-696 <![CDATA[28.69×10 -6 mm / mm / ℃]]> <![CDATA[32.14×10 -6 mm / mm / ℃]]> <![CDATA[33.16×10 -6 mm / mm / ℃]]> Punch shear strength ASTMD-732 122 MPa(-110℃) 146 MPa(-110℃) 138 MPa(-110℃) Thermal conductivity ASTMD-5470 0.243 Wm °K 0.367 Wm °K 0.321 Wm °K Creep test Internal Standards 0.026mm 0.027mm 0.027mm Curing shrinkage ASTMD-2566 0.10% 0.10% 0.10% Curing time ASTMD-2583 48h(25℃) 48h(25℃) 48h(25℃) Applicable period GB / T7123.1-2002 90min 100min 100min The test results of the performance evaluation of Examples 4-6 are shown in Table 2: Table 2 Test items Test Standards Example 4 Example 5 Example 6 Compression strength ASTMD-695 131 MPa(20℃)229 MPa(-50℃)343 MPa(-110℃)256 MPa(-196℃) 132 MPa(20℃)235 MPa(-50℃)374 MPa(-110℃)245 MPa(-196℃) 101 MPa(20℃)198 MPa(-50℃)265 MPa(-110℃)176 MPa(-196℃) Compression modulus ASTMD-695 5798 MPa(20℃)6734 MPa(-50℃)6998 MPa(-110℃)8031MPa(-196℃) 5939 MPa (20℃) 6308 MPa (-50℃) 6498 MPa (-110℃) 8981MPa (-196℃) 4876 MPa(20℃)4737 MPa(-50℃)5746 MPa(-110℃)6476MPa(-196℃) Compression toughness ASTMD-695 768 MPa(20℃)675 MPa(-50℃)1086 MPa(-110℃)605 MPa(-196℃) 702 MPa(20℃)697 MPa(-50℃)1210 MPa(-110℃)611 MPa(-196℃) 475 MPa(20℃)487 MPa(-50℃)938 MPa(-110℃)466 MPa(-196℃) Bonding of steel ASTMD-1002 15 MPa(40℃)17 MPa(20℃)13MPa(-45℃) 20 MPa(40℃)18 MPa(20℃)16MPa(-45℃) 11 MPa(40℃)13 MPa(20℃)9MPa(-45℃) Birch Bonding ASTMD-1002 4.1 MPa (40℃) 4.1 MPa (20℃) 4.1 MPa (-45℃) Adhesive surface remains bonded, breaking from the wood board 4.8 MPa (40℃) 4.3 MPa (20℃) 4.4 MPa (-45℃) Adhesive surface remains bonded, breaking from the wood board 4.2 MPa (40℃) 4.2 MPa (20℃) 4.2 MPa (-45℃) Adhesive surface remains bonded, breaking from the wood board Viscosity ASTMD-2196 Component A - 10,540cps Component B - 35cps Component A - 10,190cps Component B - 37cps Component A - 10,980cps Component B - 67cps hardness ASTMD-2583 54 Hb 50 Hbr 45 Hbr Stretch ASTMD-638 4.7% 4.8% 3.6% Coefficient of thermal expansion ASTMD-696 <![CDATA[26.78×10 -6 mm / mm / ℃]]> <![CDATA[28.99×10 -6 mm / mm / ℃]]> <![CDATA[45.66×10 -6 mm / mm / ℃]]> Punch shear strength ASTMD-732 115 MPa(-110℃) 120 MPa(-110℃) 67 MPa(-110℃) Thermal conductivity ASTMD-5470 0.279 Wm °K 0.298 Wm °K 0.498 Wm °K Creep test Internal Standards 0.025mm 0.024mm 0.029mm Curing shrinkage ASTMD-2566 0.11% 0.10% 0.11% Curing time ASTMD-2583 48h(25℃) 48h(25℃) 72h(25℃) Applicable period GB / T7123.1-2002 120min 120min 90min The test results of the performance evaluation of Comparative Examples 1-3 are shown in Table 3: Table 3 Test items Test Standards Comparative Example 1 Comparative Example 2 Comparative Example 3 Compression strength ASTMD-695 87 MPa(20℃)159 MPa(-50℃)207 MPa(-110℃)148 MPa(-196℃) 67 MPa(20℃)105 MPa(-50℃)159 MPa(-110℃)99 MPa(-196℃) 183 MPa(20℃)387 MPa(-50℃)483 MPa(-110℃)338 MPa(-196℃) Compression modulus ASTMD-695 3847 MPa (20℃) 3374 MPa (-50℃) 4478 MPa (-110℃) 5474MPa (-196℃) 3773 MPa (20℃) 3878 MPa (-50℃) 4387 MPa (-110℃) 3923MPa (-196℃) 8978MPa(20℃)9973MPa(-50℃)11874MPa(-110℃)13938MPa(-196℃) Compression toughness ASTMD-695 383 MPa(20℃)386 MPa(-50℃)539 MPa(-110℃)383 MPa(-196℃) 237 MPa(20℃)278 MPa(-50℃)387 MPa(-110℃)464 MPa(-196℃) 133 MPa(20℃)119 MPa(-50℃)89 MPa(-110℃)68 MPa(-196℃) Bonding of steel ASTMD-1002 8 MPa(40℃)7 MPa(20℃)6MPa(-45℃) 23 MPa(40℃)24 MPa(20℃)22MPa(-45℃) 3 MPa(40℃)4 MPa(20℃)2MPa(-45℃) Birch Bonding ASTMD-1002 4.0 MPa (40℃) 4.2 MPa (20℃) 4.1 MPa (-45℃) The wood board is broken 4.0 MPa (40℃) 3.9 MPa (20℃) 4.0 MPa (-45℃) Fracture at the board 2.0 MPa (40℃) 3.1 MPa (20℃) 2.5 MPa (-45℃) Fracture at the board Viscosity ASTMD-2196 Component A - 11,740 cps Component B - 98 cps Component A - 8,550 cps Component B - 152 cps Component A - 5,930 cps Component B - 10 cps hardness ASTMD-2583 50 Hbr 40 Hbr 60 Hbr Stretch ASTMD-638 4.0% 11% 3.5% Coefficient of thermal expansion ASTMD-696 <![CDATA[48.43×10 -6 mm / mm / ℃]]> <![CDATA[23.89×10 -6 mm / mm / ℃]]> <![CDATA[23.78×10 -6 mm / mm / ℃]]> Punch shear strength ASTMD-732 73 MPa(-110℃) 50 MPa(-110℃) 187 MPa(-110℃) Thermal conductivity ASTMD-5470 0.428 Wm °K 0.349 Wm °K 0.238 Wm °K Creep test Internal Standards 0.029mm 0.025mm 0.025mm Curing shrinkage ASTMD-2566 0.10% 0.10% 0.10% Curing time ASTMD-2583 72h(25℃) 72h(25℃) 72h(25℃) Applicable period GB / T7123.1-2002 120min 200min 180min The two-component LPG marine adhesive provided in this application has a high compressive load-bearing capacity, and as the temperature decreases, the compressive load-bearing capacity increases. Moreover, it still maintains good bonding performance, compressive performance, punch shear performance, hardness, etc. at different temperatures. It does not contain heavy metal salts such as nickel and cobalt, is safe and environmentally friendly, fully complies with EU ROHS standards, does not contain solvents during the processing process, and the wastewater cleaning is non-toxic and harmless. In addition to LPG ships, it can be widely used in aviation, automobiles, construction, furniture, home appliances and other fields.
[0103] It should be understood that the application of the present application is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made according to the above description, and all these improvements and changes should fall within the scope of protection of the present application.
Claims
1. A two-component LPG marine adhesive, the raw materials of which include component A and component B, characterized in that: The A component is calculated by mass percentage and includes the following components: Bisphenol A glycidyl ether epoxy resin 10-40%, alicyclic epoxy resin 2-8%, polyurethane modified epoxy resin 5-10%, rubber 1-2%, glass fiber 10-20%, silicon dioxide 10-30%, aluminum oxide 1-2%, aluminum hydroxide 5-20%, diluent 1-10%, defoamer 0.1-0.5%, silane coupling agent 0.1-0.5%, leveling agent 0.1-0.5%; The B component is calculated by mass percentage and includes the following components: Aliphatic curing agent 10-40%, alicyclic curing agent 10-40%, 4,4'-diaminodiphenylmethane 10-40%, phenolic amine 10-40%, polyether amine 10-40%.
2. The two-component LPG marine adhesive according to claim 1, characterized in that: The bisphenol A glycidyl ether type epoxy resin is a composition of E51 and E44, and the mass ratio of E51 to E44 is 1:(0.8-1.5).
3. The two-component LPG marine adhesive according to claim 1, characterized in that: The alicyclic epoxy resin is a composition of 2021P and 4221, and the mass ratio of 2021P to 4221 is 1:(0.3-0.5).
4. The two-component LPG marine adhesive according to claim 1, characterized in that: The polyurethane modified epoxy resin is a composition of DER852, DER858 and DER791, and the mass ratio of DER852, DER858 and DER791 is 1:(0.3-0.5):(0.8-1.5).
5. The two-component LPG marine adhesive according to claim 1, characterized in that: The rubber is a composition of butyl rubber, nitrile rubber and polysulfide rubber, and the mass ratio of the butyl rubber, nitrile rubber and polysulfide rubber is 1:(0.3-0.8):(0.3-0.5).
6. The two-component LPG marine adhesive according to claim 1, characterized in that: The glass fiber has a diameter of 1 μm-30 μm and a length of 10 μm-100 μm; The particle size of the silicon dioxide is 10nm~100μm; The particle size of the aluminum oxide is 10 nm to 100 μm; The particle size of the aluminum hydroxide is 10 nm to 100 μm.
7. The two-component LPG marine adhesive according to claim 1, characterized in that: The diluent is one or more of epoxy diluent HK-66, epoxy diluent 501, epoxy diluent 622, epoxy diluent 669, epoxy diluent 690, epoxy diluent X-632, epoxy diluent AGE, epoxy diluent 692, epoxy diluent X-652, epoxy diluent D-691, and epoxy diluent D-678; The defoaming agent is one or more of a polysiloxane defoaming agent, a polyether-modified silicon defoaming agent, a polydimethylsiloxane defoaming agent, and a mineral oil defoaming agent; The silane coupling agent is selected from one or more of vinyl silane coupling agents, chloroalkyl silane coupling agents, aminoalkyl silane coupling agents, epoxyalkyl silane coupling agents, and methacryloyloxyalkyl silane coupling agents; The leveling agent is one or more of a silicone leveling agent, an acrylic leveling agent, and a fluorine leveling agent; The aliphatic curing agent is one or more of diethylenetriamine, triethylenetetramine, tetraethylenepentamine and hexamethylenediamine; The alicyclic curing agent is one or more of 3,5-trimethylcyclohexane, 1,3-cyclohexanedimethylamine and 1,6-cyclohexanediamine.
8. The two-component LPG marine adhesive according to claim 7, characterized in that: The aliphatic curing agent is a composition of diethylenetriamine and triethylenetetramine, and the mass ratio of diethylenetriamine to triethylenetetramine is 1:(0.8-1.5); The alicyclic curing agent is a composition of 3,5-trimethylcyclohexane and 1,6-cyclohexanediamine, and the mass ratio of the 3,5-trimethylcyclohexane to the 1,6-cyclohexanediamine is 1:(0.8-1.5).
9. A method for preparing a two-component LPG marine adhesive according to any one of claims 1 to 8, characterized in that: The following steps are involved: The bisphenol A glycidyl ether epoxy resin, alicyclic epoxy resin, polyurethane modified epoxy resin, rubber, glass fiber, silicon dioxide, aluminum oxide and aluminum hydroxide are mixed in proportion, and then the diluent, defoamer, silane coupling agent and leveling agent are added, and stirred at room temperature to obtain the A component; The aliphatic curing agent, the alicyclic curing agent, 4,4'-diaminodiphenylmethane, phenolic amine and polyether amine are mixed in proportion and stirred at room temperature to obtain the B component.
10. An application of the two-component LPG marine adhesive according to any one of claims 1 to 8, characterized in that: Applying the two-component LPG marine adhesive to the filling connection under the support pad of the oil tank on the LPG ship comprises the following steps: Add the B component to the A component, stir and react for 30-60 minutes at 250-300 r / min, fill it into the filling connection under the support pad of the oil tank on the LPG ship, and fill the periphery with foam to prevent overflow; Fix the joint and cure at 25-35℃ for 48-72h; The mass ratio of component A to component B is 100-110:9-11.
Citation Information
Patent Citations
DE310330A
Method and device for accurately reproducing pictures, drawings, patterns and the like by hand
DE380420C